Definiteness across languages - Aguilar-Guevara, Ana; Pozas Loyo, Julia; Vázquez-Rojas Maldonado, Violeta (Studies in Diversity Linguistics, 2019)
Definiteness has been a central topic in theoretical semantics since its modern foundation. However, despite its significance, there has been surprisingly scarce research on its cross-linguistic expression. With the purpose of contributing to filling this gap, the present volume gathers thirteen studies exploiting insights from formal semantics and syntax, typological and language specific studies, and, crucially, semantic fieldwork and cross-linguistic semantics, in order to address the expression and interpretation of definiteness in a diverse group of languages, most of them understudied.